2008
DOI: 10.1186/1471-2377-8-50
|View full text |Cite
|
Sign up to set email alerts
|

Identifying people at high risk for developing sleep apnea syndrome (SAS): a cross-sectional study in a Pakistani population

Abstract: Background: Obstructive Sleep Apnea (OSA) is associated with many cardiovascular and psychiatric diseases. Day-time sleepiness is a common consequence of sleep apnea and correlates with road-traffic accidents (RTA). Pakistan has a high prevalence of factors which predispose an individual to OSA and death from RTAs are a huge burden. However there is a dearth of prevalence studies in this regard. We aim to understand local relevance of the disease and estimate the prevalence of individuals high-risk for OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…The incidence of OSAS ranged between 15 and 59% depending on the questionnaire or score used. This was much higher than the incidence reported in the literature [54][55][56] and could be due to the population studied, as our population was older and had more severe disease.…”
Section: Discussioncontrasting
confidence: 68%
“…The incidence of OSAS ranged between 15 and 59% depending on the questionnaire or score used. This was much higher than the incidence reported in the literature [54][55][56] and could be due to the population studied, as our population was older and had more severe disease.…”
Section: Discussioncontrasting
confidence: 68%
“…This observation is similar to 10% drowsy driving reported from a study in Pakistan (25), while it is lower than 12–23% in the USA and 4–14% in Europe (21). Drowsiness while driving is a major public health hazard and is associated with increased risk of motor vehicle accident and poor occupational performance.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the lack of data in Asia, the prevalence is reported to be around 2.1%-7.5% [9][10]. In Pakistan, studies conducted in Karachi, based on the Berlin questionnaire, revealed that 10%-12.4% of the population has a high risk of OSA [11][12]. Another study conducted in Lahore was intended to describe the characteristics of a small population of 30 patients diagnosed with this condition by formal overnight polysomnography (PSG) [13].…”
Section: Introductionmentioning
confidence: 99%